Abacavir Use and Risk for Myocardial Infarction and Cardiovascular Events: Pooled Analysis of Data From Clinical Trials. (20th April 2018) - Nan, Cassandra; Shaefer, Mark; Urbaityte, Rimgaile; Oyee, James; Hopking, Judy; Ragone, Leigh; Perger, Teodora; Win, Beta; Vangerow, Harald; McCoig, Cynthia; Vannappagari, Vani
Abstract: Background: Some observational studies and randomized controlled trials (RCTs) have suggested an association between abacavir (ABC) use and myocardial infarction (MI), whereas others have not. Methods: This pooled analysis of 66 phase II–IV RCTs estimates exposure-adjusted incidence rates (IRs) and relative rates (RRs) of MI and cardiovascular events (CVEs) in participants receiving ABC- and non-ABC-containing combination antiretroviral therapy (cART). The primary analysis of MI included ABC-randomized trials with ≥48-week follow-up. Sensitivity analyses of MI and CVEs included non-ABC-randomized and <48-week follow-up trials. Results: In 66 clinical trials, 13 119 adults (75% male, aged 18–85 years) were on ABC-containing cART and 7350 were not. Exposure-adjusted IR for MI was 1.5 per 1000 person-years (PY; 95% confidence interval [CI], 0.67–3.34) in the ABC-exposed group and 2.18 per 1000 PY (95% CI, 1.09–4.40) in the unexposed group. The IR for CVEs was 2.9 per 1000 PY (95% CI, 2.09–4.02) in the exposed group and 4.69 per 1000 PY (95% CI, 3.40–6.47) in the unexposed group with studies of ≥48 weeks of follow-up, with an RR of 0.62 (95% CI, 0.39–0.98). The inclusion of nonrandomized and shorter-duration trials did not significantly change the RR for MI or coronary artery disease. Conclusions: This pooled analysis found comparable IRs for MI and CVEs among ABC-exposed and -unexposed participants, suggesting no increased risk for MI or CVEs following ABC exposure in a clinical trial population. Modifiable risk factors for MI and CVEs should be addressed when prescribing ART.